The Liberal-Rejectionist Approach in Hadith Studies: A Literature Review of the Concept and Impact on Societal Intellectual Discourses: Pendekatan Liberal-Rejectionist dalam Studi Hadits: Tinjauan Literatur tentang Konsep dan Dampaknya terhadap Wacana Intelektual Masyarakat - Muttakin, Khaerul; Muhammad Aufa Yazidun Nuha; Marhumah (Jurnal Living Hadis, 2025)
The difference between today’s social reality and the historical context in which the hadith emerged necessitates a reinterpretation of several texts that are not always consistent with the dynamics of modern society. This need for adjustment has given rise to a liberal-rejectionist approach that seeks to interpret the hadith in a more historical, rational, and contextual manner, particularly with respect to issues of justice, gender bias, and universal human values. Although more relevant to contemporary society, this approach still raises methodological and epistemological issues related to the authority of the hadith and the limits of reinterpretation. In this context, this study formulates two main foci: first, how the concepts and practices of the liberal-rejectionist approach are understood in hadith studies; and second, the epistemological and social impacts of this approach on the authority of hadith and on the religious practices of Muslims. This study employs a systematic literature review following PRISMA guidelines, covering the stages of searching, selecting, extracting, and analyzing 33 scientific articles published between 2015 and 2025. The analysis employed a qualitative thematic approach to explore the conceptual, methodological, and social impact patterns that emerged in the literature. The results show that the liberal-rejectionist approach arose from the need to respond to several hadiths deemed incompatible with developments in social reality, particularly those concerning gender issues, human rights, and social justice. This approach presents a more historical and contextual reading, thereby bridging the gap between the text and changing realities. This approach is manifested in the reinterpretation, recontextualization, and rejection of certain hadiths, with attention to potential narratorial bias and the socio-historical context. These findings reveal a shift in perspective on the authority of hadith and have sparked debate between progressives and traditionalists over the legitimacy of this approach.